An Analysis of Grammatical Errors in Students’ Conversation - Febiola, Joana; Saputra, Rendy (INTERACTION: Jurnal Pendidikan Bahasa, 2022)
Compose a sentence requires grammatical aspects to make good sentences. Understanding grammar is important to make sentences correctly. This study uses a qualitative descriptive method which aims to find out the types of grammatical errors produced by UPB students when conducting interviews with other students. used to collect qualitative data is the observation method. To analyze the data used descriptive method Students are given the task of interviewing other students about the lecture period which is conducted online. Then each answer produced by the student is analyzed to find out grammatical errors that have been made. found there are 15 data in 3 types of grammatical errors, among others; there are 5 pronunciation errors, 5 tenses errors, and 5 prepotition errors. It is concluded that students still cannot make good grammatical pronunciations